Differentiation and dynamics of regional development in Central and Eastern European Countries in the period of prosperity and austerity - Smętkowski, Maciej (Studies of the Industrial Geography Commission of the Polish Geographical Society, 2015)
The aim of the paper is to demonstrate the scale of regional disparities and the dynamics of regional development in Central and Eastern European Countries (CEECs). The article attempts to answer the following research questions: a) does regional development of the CEE countries corroborate the J. G. Williamson (1965) hypothesis concerning the relationship between the level of national income and the extent of regional disparities, b) what are the main reasons for changing the scale of regional differences, and c) how economic crisis has affected the dynamics of regional development. Empirical studies have shown a decrease in the rate of regional divergence with increasing income levels in different countries. This occurred under the conditions of regional economic structure petrification - especially after excluding capital city regions from the analysis - which may indicate a balance between spread and backwash effects in the period of economic prosperity - especially in the years 2004-2008. The outcome of the first phase of the economic crisis was quite patchy regarding regional development pattern, but with noticeable better adaptability of majority of capital city regions.